Comparative Evaluation of Various Temperature Changes on Stress Distribution in Class II Mesial-occlusal-distal Preparation restored with Different Restorative Materials: A Finite Element Analysis - Srivastava, Binita (Int J Clin Pediatr Dent, 2018)
INTRODUCTION: The principal goal of dentistry is to maintain and improve the quality of life of the dental patients. As many of these objectives require the replacement or alterations of the existing tooth structure, the main challenge for centuries has been the development and selection of biocompatible materials that can withstand the unique conditions of the oral environment. Finite element analysis (FEA) is a modern technique of numerical stress analysis that has become a solution to the task of predicting failure due to unknown stresses by showing problem areas in a material and allowing designers to see all of theoretical stresses within. AIMS AND OBJECTIVES: To evaluate and compare the effect of various temperature changes on the stress distribution, in class II mesial-occlusal-distal (MOD) cavity when restored with different restorative materials, using the finite element method (FEM). MATERIALS AND METHODS: Using FEA, various thermal stresses generated in class II MOD lesion using different restorative materials were studied. RESULTS: The computer-generated models of intact tooth and teeth restored with the different restorative materials were designed, and thermal stress at different temperatures was observed when subjected to the thermal loads of 5°C, 20°C, 36°C, and 55°C. From the results of the study, it can be concluded that glass ionomer cement (GIC) performed best, followed by intact tooth, composite resin, silver amalgam, and zinc oxide eugenol cement. CONCLUSION: Restoration of class II MOD lesions with materials of lower modulus of elasticity and lower coefficient of thermal expansion will enable better stress distribution. How to cite this article: Srivastava B, Devi NN, Gupta N, Singh R. Comparative Evaluation of Various Temperature Changes on Stress Distribution in Class II Mesial-occlusal-distal Preparation restored with Different Restorative Materials: A Finite Element Analysis. Int J Clin Pediatr Dent 2018;11(3):167-170.